The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1084/jem.20141030
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CTLA-4 on regulatory T cells during adulthood leads to resistance to autoimmunity

Abstract: Paterson et al. demonstrate that, in contrast to CTLA-4 germline knockout mice, conditional deletion on T reg cells during adulthood confers protection from EAE and does not increase resistance to tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 85 publications
10
158
2
Order By: Relevance
“…53,54 In this model, single agent RON i or aCTLA-4 treatment did not affect subcutaneous tumor growth (Fig S8a-c) . However, while tumor shrinkage was not observed in any of the mice, combination of RON i and aCTLA-4 significantly reduced the tumor growth rate (Fig S8c) , suggesting RON inhibition can potentiate immunotherapy responses in other types of cancers.…”
Section: Resultsmentioning
confidence: 79%
“…53,54 In this model, single agent RON i or aCTLA-4 treatment did not affect subcutaneous tumor growth (Fig S8a-c) . However, while tumor shrinkage was not observed in any of the mice, combination of RON i and aCTLA-4 significantly reduced the tumor growth rate (Fig S8c) , suggesting RON inhibition can potentiate immunotherapy responses in other types of cancers.…”
Section: Resultsmentioning
confidence: 79%
“…This expanded Treg compartment is highly consistent with the known impact of CTLA-4 deficiency on Treg homeostasis in mice. 20,21,26 Because in LRBA deficiency CTLA-4 protein is incorrectly trafficked to lysosomes, we also assessed CTLA-4 expression in the presence of BafA to prevent lysosomal degradation. As shown in Figure 5E, both control individuals and those carrying CTLA-4 mutations showed a 1.5-fold to twofold increase in CTLA-4 in response to BafA.…”
Section: Distinguishing Ctla-4 Mutations From Lrba Deficiencymentioning
confidence: 99%
“…Accordingly, mice completely deficient in CTLA-4, and those conditionally deficient only in Tregs, develop wide-ranging and typically fatal autoimmunity [17][18][19] but with some variation. 20,21 We recently identified a mechanism of action whereby CTLA-4 acts to capture and remove its ligands from antigen-presenting cells by a process known as transendocytosis. 22 Because T-cell costimulation via CD28 is triggered by these same ligands (CD80 and CD86), CTLA-4 therefore acts to regulate CD28 stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…We and others found that CTLA--4 knockout mice exhibit a dramatically expanded Treg population that show increased expression of the proliferation marker Ki67 [40,47]. This phenotype is recapitulated by inducible deletion of CTLA--4 in adult mice [74,75] and in line with this, treatment of wildtype mice with blocking anti--CTLA--4 antibody augments Treg numbers in lymphoid tissues [76,77]. The proliferation of Treg is known to be positively regulated by CD28 signaling [44,45] suggesting a model in which CTLA--4 regulates Treg proliferation by controlling access of CD28 to their shared ligands (CD80 and CD86).…”
Section: Ctla--4 and Treg Homeostasismentioning
confidence: 63%